Ten new species in the southern African genus Heliophila (Brassicaceae; Cruciferae) - Al-Shehbaz, Ihsan A. (Phytotaxa, 2020)
Ten new South African species of Heliophila (H. astyla, H. biseriata, H. clarkii, H. crassistyla, H. goldblattii, H. magaliesbergensis, H. pseudoeximia, H. roggeveldensis, H. volkii, and H. xylopoda) are described, illustrated, and their relationships and distinguishing characters from nearest relatives are discussed. The chromosome number 2n = 22 for H. goldblattii is reported. Four species (H. astyla, H. crassistyla, H. volkii, H. xylopoda) are endemic to the Western Cape, three (H. clarkii, H. goldblattii, H. pseudoeximia) to the Northern Cape, two (H. biseriata, H. roggeveldensis) in both provinces, and one (H. magaliesbergensis) in Gauteng Province. All species of the genus are native to South Africa, with the ranges of some extending in neighboring Namibia, Lesotho, and Swaziland.